(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
The study was aimed at investigating the effects of Brachystegia gum (BG)-egg albumin (EA) mixture as binding agent on the qualities of metronidazole tablets. BG and EA were mixed at different ratios to generate fifteen binder mixtures (F1-F15), from which F1-F5, F6-F10 and F11-F15 were used at 2%, 4% and 6% w/w respectively to formulate metronidazole granules by wet granulation. The granules after micromeritic characterization were subsequently compressed into tablets. Quality control tests conducted on the tablets include: hardness, friability, weight uniformity and dissolution studies. Results reveal that granules flow rates ranged from 3.02 g/s (F4) to 4.73 g/s (F1); angle of repose ranged from 29.06° (F12) to 35.93° (F3); Carr’s index values were between 7.49% (F9) and 25.43% (F12), while Hausner’s ratio ranged from 1.08 (F9) to 1.34 (F12). Tablet hardness values were between 3.65±0.47 (F2) and 5.95±0.60 (F11). Tablets friability values were of magnitude ranging from 0.84 (F11) t0 21.73 (F1). The result of weight variation test revealed that only four batches (F4, F6, F9 and F15) met compendia specifications. Among the metronidazole tablet formulations, those containing binder at 2% w/w released the highest amount of drug, giving up to 90% drug release in 6 h. The least amount of metronidazole was released by tablets formulated with binders at 6% w/w from which only about 30% of drug was released in 6 h. The BG-EA mixture was found useful in imparting slow release profile on metronidazole tablets, which is desirable for some tablet formulations.